The Use of Game Media Engklek for Introducing The Value of Nationalism in Elementary School - Nina Nurhasanah; Iva Sarifah (Universitas Pendidikan Ganesha, 2023)
Based on the needs analysis, it was found that there still needed to be more variety of media used by teachers and students to form character in Civics learning in elementary schools. The right learning media will make it easier for teachers to shape the character of students in elementary schools. Therefore, this study aims to produce Civics learning media in forming the character of loving the motherland in elementary schools with field and effectiveness tests. The research method uses design and development. This type of research is development. Methods of data collection using observation, interviews, and questionnaires. The research subjects were material, media, and language experts using validation sheets. The test subjects were 18 grade IV students. The instruments used in data collection were questionnaires, interview guides, and documents. The technique used to analyze the data is descriptive qualitative and quantitative analysis. The results were that Engklek Karkater (EKA) was effective as a Civics learning medium for introducing the value of nationalism in elementary schools. The output of the research results is in the form of traditional game media that is scientifically feasible and has been tested for its effectiveness, along with a guidebook for using the Engklek Karanter game media to introduce the character values of Nationalism in Elementary Schools. This study implies that teachers can use the character crank game media to introduce the character values of love for the motherland (nationalism) which is the goal of Civics subjects.